Macrophage migration inhibitory factor (MIF) gene -173 G>C polymorphism and its relationship to coronary artery disease and type 2 diabetes - Neslihan Çoban; Aycan Fahri Erkan; Berkay Ekici; Maide Kaşit; Nihan Erginel Ünaltuna; Eren Vurgun (KARE Publishing, 2019)
Objective: Recent studies indicate that macrophage migration inhibitory factor (MIF) is a potent proinflammatory cytokine which mediates the inflammatory process during atherosclerosis. The purpose of the study was to investigate an association between MIF gene polymorphism and type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD) in the Turkish population. Methods: A total of 139 unselected Turkish patients with significant CAD (coronary lesion with 50-100% stenosis) and 120 control participants (coronary lesion with <30% stenosis) were genotyped for MIF rs755622 polymorphisms using hybridization probes in a Roche LightCycler 480 Real-Time Polymerase Chain Reaction 480 device. Blood samples were drawn before coronary angiography. Gensini and SYNTAX scores were used to determine the angiographic extent and severity of CAD. Results: When the groups were stratified according to T2DM, polymorphism of MIF was not associated with T2DM in CAD patients (p>0.05). In the same subgroups, carriers of the MIF common allele in the control group demonstrated a protection against developing T2DM compared with noncarriers (p<0.05). In addition, MIF C allele carriage was associated with higher glycated hemoglobin (HbA1c) in the T2DM group (p=0.038). Conclusion: The MIF rs755622 polymorphism was associated with HbA1c. This result suggests that the MIF gene variant may contribute to CAD risk through diabetes in the Turkish population.